2020
DOI: 10.1186/s12911-020-01143-9
|View full text |Cite
|
Sign up to set email alerts
|

Data mining application to healthcare fraud detection: a two-step unsupervised clustering method for outlier detection with administrative databases

Abstract: Background: The healthcare sector is an interesting target for fraudsters. The availability of a great amount of data makes it possible to tackle this issue with the adoption of data mining techniques, making the auditing process more efficient and effective. This research has the objective of developing a novel data mining model devoted to fraud detection among hospitals using Hospital Discharge Charts (HDC) in Administrative Databases. In particular, it is focused on the DRG upcoding practice, i.e., the tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…(a) (Francis, 2020 ) Upcoding Intentionally coding a health claim based on an inaccurate use of codes to obtain greater economic value. (b) (Gasquoine & Jordan, 2009 ; Massi et al, 2020 ; Palutturi et al, 2019 ; Phillipsen et al, 2008 ; Sheffali & Deepa, 2019 ) Unperformed or billing for services not provided Known as phantom billing, claims are presented for medical services, medications, medical devices not delivered to the patient. (c) (Aral et al, 2012 ; Bauder & Khoshgoftaar, 2020 ; Bayerstadler et al, 2016 ; Brooks et al, 2012 ; Dolan & Farmer, 2016 ; Gasquoine & Jordan, 2009 ; Jou & Hebenton, 2007 ; Lee et al, 2016 ; Li et al, 2008 ; Palutturi et al, 2019 ; Perez & Wing, 2019 ; Phillipsen et al, 2008 ; Smith et al, 2013 ; Yang, 2003 ) Misrepresenting the diagnosis or procedure to justify payment Manipulation of procedures, diagnoses, requests, complaints, dates, frequency, duration or description of the services provided.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(a) (Francis, 2020 ) Upcoding Intentionally coding a health claim based on an inaccurate use of codes to obtain greater economic value. (b) (Gasquoine & Jordan, 2009 ; Massi et al, 2020 ; Palutturi et al, 2019 ; Phillipsen et al, 2008 ; Sheffali & Deepa, 2019 ) Unperformed or billing for services not provided Known as phantom billing, claims are presented for medical services, medications, medical devices not delivered to the patient. (c) (Aral et al, 2012 ; Bauder & Khoshgoftaar, 2020 ; Bayerstadler et al, 2016 ; Brooks et al, 2012 ; Dolan & Farmer, 2016 ; Gasquoine & Jordan, 2009 ; Jou & Hebenton, 2007 ; Lee et al, 2016 ; Li et al, 2008 ; Palutturi et al, 2019 ; Perez & Wing, 2019 ; Phillipsen et al, 2008 ; Smith et al, 2013 ; Yang, 2003 ) Misrepresenting the diagnosis or procedure to justify payment Manipulation of procedures, diagnoses, requests, complaints, dates, frequency, duration or description of the services provided.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 26 studies that explained 15 factors, the most referenced factors are audit, supervision and control, with 8 studies, while 6 studies explain the general characteristics of the provider. The factors supported by applied studies that have shown influences in favour of the HIF occurring are the general characteristics of the provider (Herland et al, 2018 ; Kang et al, 2010 ), in favour of the HIF decrease (Vian, 2020 ), ambivalent (Massi et al, 2020 ); the management and policy of complaints show results that contribute to HIF (Vian, 2020 ) and ambivalent results (Lesch & Baker, 2013 ); while that the reputation shows ambivalent influence (Tseng & Kang, 2015 ), the audits, supervision and control contributes to reducing the HIF (Kang et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Zhao et al (2020) used data mining to study the risk factors that can predict IHD during pheochromocytoma surgery, and observed that data mining techniques are increasingly being used in clinical and medical decision-making to provide continuous support for the diagnosis, treatment, and prevention of disease. Massi et al, 2020 noted that the healthcare industry is an interesting target for fraudsters. The availability of large amounts of data makes it possible to solve this problem through the use of data mining techniques, thereby making the review process more effective.…”
Section: Background and Literature Reviewmentioning
confidence: 99%